The use of the three-pronged Mayfield head clamp resulting in an intracranial epidural hematoma in an adult patient - Lee, Michael J. (Springer-Verlag, 2010)
Complications from the use of a three-pronged Mayfield head clamp have been reported in the pediatric population, usually in children with intracranial pathology or hydrocephalus resulting in a thinner skull. We report the occurrence of an intracranial epidural hematoma in an adult patient without any prior intracranial pathology after the use of a Mayfield head clamp during posterior cervical spine surgery. The purpose of the study was to report an occurrence of epidural hematoma from the use of a Mayfield head clamp in an adult patient and to review the literature. The diagnosis of intracranial epidural hematoma should be considered in the presence of persistent headache and nausea after the use of a head clamp in spinal or intracranial surgery.